Raids and rescues - Chick, Bryan (New York, NY Greenwillow Books, an imprint of HarperCollinsPublishers, 2013)
Noah, Megan, Richie, and Ella must navigate a maze of never-ending aquariums in the Secret Zoo to rescue their animal friends
1
Keywords: Friendship -- Fiction; Human-animal relationships -- Fiction; Rescues -- Fiction; Secret societies -- Fiction; Zoo animals -- Fiction; Zoos -- Fiction